THE HYDROTHERMAL CHEMISTRY OF FLUORIDE IN SEAWATER - Seyfried W.E.; Ding K. (My University, 1995)
A series of hydrothermal experiments were performed at temperatures from 150-350°C (500 bars) to assess the effect of temperature on the solubility of F in seawater. Changes in dissolved F were measured along with pH and the major element chemistry of seawater. The major element chemistry of seawater changes with temperature owing to homogeneous nucleation and precipitation of carbonate, sulfate, and hydroxyl-sulfate minerals. Thus, to identify better the role such minerals play on F variability, predicted and measured changes in major elements were assessed simultaneously with temperature dependent changes in dissolved F.Dissolved F was observed to decrease at temperatures from 150-250°C. At temperatures greater than 250°C, however, dissolved F concentration increased and at 300°C, F achieved a concentration equivalent to that of unaltered seawater. This suggests that a F-rich mineral precipitates at temperatures in the vicinity of 250°C, and then entirely dissolves at temperatures greater than 250°C. Temperature dependent changes in dissolved F are best accounted for by 2F- # CO-23 and F- # OH- exchange between the fluid and magnesium carbonate and magnesium-hydroxide-sulfate-hydrate (MHSH) phases, respectively. At 250°C, F-(aq) and MgF+(aq) dominate the distribution of F-bearing aqueous species, while at temperatures greater than this, HF°(aq) dominates. Thus, the sharp decrease in F-(aq) ion activity at temperatures =< 250°C, may account for the dissolution of F-bearing minerals.Results from the seawater heating experiments show that F is a particularly reactive element and precipitates as a component in a number of different minerals over a range of temperatures. Reactions of this sort likely occur during seawater recharge of subseafloor hydrothermal systems and limit the amount of seawater derived F which can participate in alteration processes at relatively deep crustal levels. Results of thermodynamic calculations, however, indicate that rock-fluid interaction processes, especially at low to moderate temperatures, can also provide sinks for F in the form of fluor-components in basalt alteration phases, such as F-talc. Considering the tendency of F to partition into the fluid with increasing temperature, the relative absence of F in hot spring fluids suggests the existence of phases with unusually strong affinity for F in subseafloor reaction zones at mid-ocean ridges. Additional experiments are needed to confirm results of theoretical calculations involving F partitioning during fluid-mineral equilibria at elevated temperatures and pressures.